COMPARAÇÃO DOS MÉTODOS MANUAIS E VIA SOFTWARE PROELÉTRICA DOS PROJETOS DE INSTALAÇÕES ELÉTRICAS E CÁLCULO LUMINOTÉCNICO - Silva, Pedro Henrique Fontes; Costa, Iara Ferreira de Rezende; Muniz, Mariana Cotta (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Aiming to provide energy to the user efficiently and safely, supported by the Brazilian standards and by the ones provided by energy supplies concessionaries, these project aims to elaborate electrical installation projects, from an architectural project idealized on a real site, by different methods to comparison. Those projects were developed manually and by the PRO-Elétrica software, presenting the main divergences and convergences found in the elaboration of facilities. Another tool developed through the methods, the luminotechnical calculation, is extremely important and indispensable in buildings, seeking the visual comfort. Therefore, with the projects done, we have that, for the electrical installation projects, is considered feasible to use the initial calculations up until the distribution of the circuits by the manual method, combined with the software, through the automatic distribution and generation of several points, tables and diagrams, among others, making indispensable the mutual collaboration of methods. For the luminotechnical project, the use of the software alone is highly recommended, considering time factors and accuracy of results. However, the results achieved corresponded to the initial expectations, with the feasibility of using the methods by simplifying the procedures and improving the facilities.